MAP4K3/GLK inhibits Treg differentiation by direct phosphorylating IKKβ and inducing IKKβ-mediated FoxO1 nuclear export and Foxp3 downregulation - Chi, Jyun-Ni; Yang, Jhih-Yu; Hsueh, Chia-Hsin; Tsai, Ching-Yi; Chuang, Huai-Chia; Tan, Tse-Hua (Theranostics, 2022)
Rationale: GLK (MAP4K3) activates PKCθ-IKKβ axis in T-cell activation and induces IL-17A-mediated autoimmune diseases. Attenuation of Treg differentiation and function by GLK could also contribute to autoimmune diseases. Methods: We analyzed the roles of GLK and IKKβ in Treg differentiation and function using T-cell-specific GLK transgenic mice and IKKβ conditional knockout mice. The mechanism of GLK/IKKβ-mediated attenuation of Treg differentiation/function was studied by chromatin-immunoprecipitation, reporter assays, in vitro kinase assays, protein-protein interaction assays, mass spectrometry, confocal microscopy, flow cytometry, and single-cell RNA sequencing (scRNA-seq) analysis. Results: We found that GLK signaling inhibited Foxp3 transcription by blocking the function of the transcription factor FoxO1. Mechanistically, GLK directly phosphorylated and activated IKKβ at Ser733 in a PKCθ-independent manner. The phospho-IKKβ Ser733 induced FoxO1 Ser319 phosphorylation and nuclear export, leading to Foxp3 downregulation. Consistently, scRNA-seq analyses showed that Foxp3 mRNA levels were inversely correlated with FoxO1 mRNA levels in GLK transgenic CD4+ T cells. Conclusions: GLK-IKKβ-FoxO1 signaling axis inhibits Foxp3 transcription, leading to reduction of Treg differentiation and suppressive activity, as well as induction of autoimmune disease.